O enforcement contratual no Brasil: uma análise das decisões do TJSP e TJRS sobre o contrato de factoring - El Dib, Gabriela Gentille Menna Barreto (2014)
The New Institutional Economics gave a prominent role to institutions, classifying them as the "rules of the game" in a society. A part of this literature focuses on analysing the link between contractual enforcement of judgments handed down by the courts and its impact on the economic development of nations, in particular developing countries. In Brazil, this debate became relevant in the late 1990s due to social researches conducted with judges, which has attested that the courts tend to sacrifice judicial predictability in favour of social justice. In this context, some Brazilian economists pointed out the hypothesis that the Brazilian courts present an anticreditor bias, which can be translated as the court’s position to rule in favour of the debtors. This results in the maintenance of high interest rates in the country and the absence of a long term credit market. Within this context, a specific segment was selected: factoring, to develop a substantive qualitative empirical research in order to (i) investigate the enforcement of contractual decisions, and (ii) test whether there is the existence of an anticreditor bias by the Courts of Justice of São Paulo and Rio Grande do Sul.